Peningkatan Kinerja MPPT Menggunakan Kontrol PWM Fuzzy dengan Tuning PID - Adhi Kusmantoro; Margono Margono (Jurnal Rekayasa Elektrika, 2020)
Utilization of sunlight using solar panels as power plants began to be developed to reduce the use of fossil fuels. The purpose of this study is to design an MPPT model with PV sources. The PID controller is used to improve MPPT performance in regulating the boost converter, while the PID value is set with fuzzy logic. Research methods include simulation design, hardware, load capacity calculation, and fuzzy logic design. The trial was conducted using an electric load in the house. The results of previous studies, using PID control generated 88.77% efficiency. The results of the study using PID control that is regulated by fuzzy logic produces 95.79% efficiency. This method is also able to improve the output of the boost converter voltage, so that with this method the boost converter output voltage is better when compared to other methods.